Growth performance of thai pangus (Pangasius hypophthalmus) in polyculture system using different supplementary feeds (University Journal of Zoology, Rajshahi University, 2009)
Thai pangus polyculture with carps has been increasing for its high potential, however very few attempts were made to compare its growth using different types of feed. A research was undertaken to assess the effect of three types of feed on growth of Thai pangus (Pangasius hypophthalmus) and rohu (Labeo rohita) in polyculture system for 11 months from 15 May 2005 to 15 April 2006 in Khulna. Growth performance using Hand-made Feed (F1) was compared with two commercial fish feed, Sunney Feed (F2) and Saudi-Bangla Feed (F3) in three respective treatments of T1, T2 and T3. All treatments were carried out in triplicate at 24700/ha for Thai pangus and 4940/ha for rohu. Average initial weight of Thai pangus and rohu were 4.5 and 33.5g respectively. Growth performance was influenced by feed type. Average final weight of Thai pangus and rohu were 820 and 710; 846 and 770; and 872 and 717g with specific growth rate 1.58 and 0.93; 1.59 and 0.95 and 1.60 and 0.93 % day -1 in T1, T2 and T3 respectively. Feed conversion ratio was estimated 2.3 in T1, 2.1 in T2 and 1.96 in T3. The result showed a typical increasing trend of final weight and specific growth rate of Thai pangus along with the increasing of feed protein level. But rohu showed highest growth in T2 where protein level was 26-30% which was lower than that of T3 (Protein level 28-32%). The study suggests that suitable protein level and quality feed is required for adequate growth of fish. Key words: Feed, Thai pangus, Polyculture, Growth. doi:10.3329/ujzru.v27i0.1956 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 59-62